Personal Hygiene Learning in Preschool Classroom - Arifiyanti, Nurul; Prasetyo, Iis (Indonesian Journal of Early Childhood Education Studies, 2018)
The present study examined: what personal hygiene habits which preschool’s teacher incorporated into their classroom, how they incorporated it into the daily activities, and how often such activities were done. A descriptive study was designed to examine the personal hygiene learning in preschool during August-October 2017 in Java, Indonesia. A total of 29 preschool’s teacher asked to join this study. An interviewed guideline was used to collect the information. A thematic framework was sorted from verbatim transcripts. The results of the study indicate that the most incorporate activities were hand washing, showering, toilet training, cleaning the ears, and cleaning the hairs. The least incorporated personal hygiene activities were cutting the nails and cover the mouth when getting flu and cough. Personal hygiene activities such as hand washing were used to keep our body healthy and far from bacteria were the most reason used by the teacher to explain to the children how important of personal hygiene was. The study recommends the need to make personal hygiene learning education as the core component of preschool teacher’s training. So, they can incorporate this learning into preschool’s curriculum.